Reconstructing Transformational Leadership through Islamic Values: A Model for Improving Institutional Performance in Islamic Education - Mundiri, Akmal; Sain, Zohaib Hassan; Khomairohtusshiyamah, Unzilah (Mozaic : Islam Nusantara, 2025)
This study aims to reconstruct transformational leadership through the integration of Islamic values, offering a contextual model for enhancing the performance of Islamic educational institutions. The primary focus is to combine the core principles of transformational leadership with Islamic teachings to form a leadership framework that aligns with the spiritual, ethical, and cultural foundations of Islamic education. Using a qualitative approach and a case study design, research was conducted in several Islamic educational institutions across Indonesia. Data were collected through in-depth interviews, participant observation, and document analysis. The research findings indicate that Islamic values such as sincerity (ikhlas), trustworthiness (amanah), justice (‘adl), and deliberation (shura) reinforce the four key dimensions of transformational leadership: idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. These values do not replace transformational leadership elements but enrich and contextualize them, leading to improved institutional performance in managerial, academic, and spiritual aspects. The implications of this study underline the significance of internalizing Islamic values within leadership practices to build a productive, ethical, and spiritually grounded organizational culture. This integrated model can serve as a practical and theoretical reference for developing effective, authentic, and sustainable leadership in Islamic educational settings.